Kinetic study of acetic acid production from banana stem waste using soil bacteria, Bacillus Thuringiensis - Aiza, Abd Rahman (2013)
Nowadays, the demand of acetic acid in the world was about 7.8 million tons in 2005. The largest consumer of acetic acid was vinyl acetate with 42.4 % of consumption. Recently, most of the acetic acid in chemical industries was produced synthetically. The process required high chemical consumption. So, the anaerobic fermentation process was another alternative method to produce acetic acid. The anaerobic fermentation required raw material as substrates and microbes. In Malaysia, there are millions abandon lignocellulosic waste that can be use as substrates. Banana stem waste (BSW) is type of lignocelluloses waste contains cellulose, hemicelluloses and lignin. These renewable sources can be used in anerobic fermentation to produce acetic acid. Bacillus Thuringiensis is one of the soil bacteria that had ability to digest the banana stem waste. This research is about to study the kinetic parameter of acetic acid production from banana stem waste using soil bacteria; Bacillus Thuringiensis. This experiment was conducted in two different medium. First medium was banana stem medium. Second medium was glucose medium which later was used as references to compare with banana stem waste medium. First step was revival of the pure culture of Bacillus Thuringiensis. Second step was inoculums preparation. Third step was fermentation process. The anaerobic fermentation process was conducted in 72 hours at temperature of 30 oC. The biomass was separated using microcentrifuge. Glucose utilization concentration is measure using glucose analyzer. And acaetic acid produced concentrations were determined using High Performance Light Chromatography. After the data has been collected, the kinetic parameter will be determined using Kinetic Modeling Equation. The Runge-Kutte Fourth Order method is used to solve the model. The calculation is done by using Microsoft Excel Solver Software to determine the kinetic parameter in the kinetic modeling equation. The kinetic parameter obtained for both banana stem waste medium and glucose medium are slightly different. There are actually 7 kinetics parameters from banana stem medium and glucose medium has been solved. Firstly, for BSW medium, k1 is 0.5004 day-1, k2 is 0.0576 g L-1 day-1, k3 is 0.6197 g L-1, k4 is 0.1295 g L-1 day-1, k5 is 0.92897 g L-1, k6 is 0.0546 g L-1 day-1 and k7 is 0.0001 g L-1. For glucose medium, k1 is 0.4667 day-1, k2 is 0.0671 g L-1 day-1, k3 is 0.023 g L-1, k4 is 0.2382 g L-1 day-1, k5 is 0.538 g L-1, k6 is 0.114 g L-1 day-1 and k7 is 0.001 g L-1.The percentage relative error of BSW medium was 0.44 and 0.77 in glucose medium. The yield of acetic acid produced from BSW medium was 2.98 g acetic acid/ g BSW and yield of acetic acid produce from glucose medium was 10.2 g Acetic Acid/ g glucose. The kinetic parameter is studied to predict the performance of the system such as stability of the system and the effluent of the system. So, the kinetic parameter will be used in scaling up the feed, biomass and production of the system.